Test-Retest Reliability of Traumatic Brain Injury Outcome Measures: A Traumatic Brain Injury Model Systems Study. Issue 5 (September 2017) - Bogner, Jennifer A.; Whiteneck, Gale G.; MacDonald, Jessica; Juengst, Shannon B.; Brown, Allen W.; Philippus, Angela M.; Marwitz, Jennifer H.; Lengenfelder, Jeannie; Mellick, Dave; Arenth, Patricia; Corrigan, John D.
Abstract : Objective: Evaluate the test-retest reliability of measures that comprise the Traumatic Brain Injury Model Systems follow-up data set. Participants: A total of 224 persons with a moderate-severe traumatic brain injury (TBI) enrolled in the Traumatic Brain Injury Model Systems National Database. Design: Following standard administration of the follow-up interview, a second interview was administered 14 to 28 days later using the same interviewer and the same mode of administration. Main Measures: Traumatic Brain Injury Model Systems follow-up interview that includes 66 variables comprised ( a ) single item measures of demographics; employment; general health as well as specific health conditions; rehospitalization; tobacco, alcohol, and other drug use; transportation; and mental health and ( b ) multi-item instruments: FIM; Participation Assessment With Recombined Tools-Objective; Disability Rating Scale; Glasgow Outcome Scale—Extended; Supervision Rating Scale; Satisfaction With Life Scale; TBI Quality of Life Anxiety and Depression items; and The Ohio State University TBI Identification Method. Results: Intraclass correlation coefficient values ranged from 0.65 to 0.99, weighted kappa values ranged from 0.54 to 0.99, and kappa values ranged from 0.43 to 1.00. Four kappa/weighted kappa estimates fell below 0.60: arrested, psychiatric hospitalization, number of days not in good physical health, and rating of general emotional health. Conclusions: With few exceptions, good to excellent test-retest reliability estimates were obtained. The findings support the use of these measures in prior and future studies and indicate that persons with moderate-severe TBI can provide reliable self-report.